2019
DOI: 10.1080/09546634.2019.1623860
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician preferences for atopic dermatitis injection treatments in Japan

Abstract: Background: Recently, biologic agents administered as a subcutaneous injection have been introduced as treatment options for atopic dermatitis (AD). Biologic treatments differ considerably from traditional topical and systemic anti-inflammatory treatments, and it is unclear how this may impact patient and physician preferences for treatments. Objective: To examine the treatment preferences for new injection treatments of patients and physicians. Methods: Discrete choice experiment methodology was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…As previously reported, the safety profile of abrocitinib in JADE COMPARE was consistent with previous studies, and abrocitinib demonstrated rapid improvement in the signs and symptoms of AD compared with placebo 16 . Swift and clinically meaningful improvements in severity of patient‐reported signs and symptoms are desirable in patients with AD 13,26,27 . More than half of patients with moderate‐to‐severe AD have inadequately controlled disease despite the use of currently available therapies 28 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously reported, the safety profile of abrocitinib in JADE COMPARE was consistent with previous studies, and abrocitinib demonstrated rapid improvement in the signs and symptoms of AD compared with placebo 16 . Swift and clinically meaningful improvements in severity of patient‐reported signs and symptoms are desirable in patients with AD 13,26,27 . More than half of patients with moderate‐to‐severe AD have inadequately controlled disease despite the use of currently available therapies 28 .…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, dupilumab is administered by subcutaneous injection; many patients prefer therapies with less invasive routes of administration (i.e. oral administration) 13 . Many more systemic treatments are becoming available for the treatment of moderate‐to‐severe AD, with baricitinib, tralokinumab, upadacitinib, and abrocitinib recently gaining approval in some geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the results of a similar study performed in Japan, in which physicians were more likely to value the efficacy of biological therapies in the treatment of AD [ 38 ]. In terms of AEs, another study in the USA comparing physician and patient preferences reported that the former are more concerned with the possibility of long-term AEs than the latter [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…This was one of the first studies (first in the United States and the United Kingdom) to our knowledge to assess patient preferences for systemic treatment options for moderate-to-severe AD. A study conducted in Japan, which assessed preferences among patients with moderate-tosevere AD focused more on differences between preferences of patients and physicians, specifically regarding attributes of injection treatments [23]. Qualitative interviews from our study indicated that for systematic treatments, respondents value probability of skin clearance, time to onset of itch relief, convenient dosing/administration schedule, and avoidance of safety risks.…”
Section: Discussionmentioning
confidence: 87%
“…Unfortunately, no data exist on patient preferences for systemic AD treatments in the United States and Europe. One study was conducted in Japan, which reported that the top three attributes for the patients are risk of mild side effects, time until response, and efficacy of reducing itching; however, this study focused more on the differences between the top attributes for patients and physicians for injection treatments [23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%